Long-read sequencing sheds light on key bacteria contributing to deadwood decomposition processes - Richy, Etienne; Thiago Dobbler, Priscila; Tláskal, Vojtěch; López-Mondéjar, Rubén; Baldrian, Petr; Kyselková, Martina (Environmental microbiome, 2024)
BACKGROUND: Deadwood decomposition is an essential ecological process in forest ecosystems, playing a key role in nutrient cycling and carbon sequestration by enriching soils with organic matter. This process is driven by diverse microbial communities encompassing specialized functions in breaking down organic matter, but the specific roles of individual microorganisms in this process are still not fully understood. RESULTS: Here, we characterized the deadwood microbiome in a natural mixed temperate forest in Central Europe using PacBio HiFi long-read sequencing and a genome-resolved transcriptomics approach in order to uncover key microbial contributors to wood decomposition. We obtained high quality assemblies, which allowed attribution of complex microbial functions such as nitrogen fixation to individual microbial taxa and enabled the recovery of metagenome-assembled genomes (MAGs) from both abundant and rare deadwood bacteria. We successfully assembled 69 MAGs (including 14 high-quality and 7 single-contig genomes) from 4 samples, representing most of the abundant bacterial phyla in deadwood. The MAGs exhibited a rich diversity of carbohydrate-active enzymes (CAZymes), with Myxococcota encoding the highest number of CAZymes and the full complement of enzymes required for cellulose decomposition. For the first time we observed active nitrogen fixation by Steroidobacteraceae, as well as hemicellulose degradation and chitin recycling by Patescibacteria. Furthermore, PacBio HiFi sequencing identified over 1000 biosynthetic gene clusters, highlighting a vast potential for secondary metabolite production in deadwood, particularly in Pseudomonadota and Myxococcota. CONCLUSIONS: PacBio HiFi long-read sequencing offers comprehensive insights into deadwood decomposition processes by advancing the identification of functional features involving multiple genes. It represents a robust tool for unraveling novel microbial genomes in complex ecosystems and allows the identification of key microorganisms contributing to deadwood decomposition.
Keywords: Deadwood microbiome; Biosynthetic gene cluster; Nitrogen fixation; Carbohydrate-active enzyme; Microbial decomposition; Metagenomics; Metagenome-assembled genome